TRAUMATIC BILATERAL FEMORAL FRACTURE AND CONCURRENT VASCULAR INJURY IN A 2-YEAR-OLD CHILD - A RARE CASE REPORT - Sahito , Badaruddin; Kumar, Dileep; Altaf, Hina; Zehra, Asmat; Syed, Bushra (Journal of Ayub Medical College Abbottabad, 2023)
Fractures are an ordinary consequence of trauma. Paediatric fractures are rather uncommon because the bony framework is still in its growth phase and therefore compliant to such traumas. The incidence of vascular injuries is also low lying (<1%) in this age group. Nevertheless, management and recovery continue to be a challenge. In this case report, we discuss a 2-year-old child with a traumatic bilateral femoral fracture, a tibial fracture with added vascular injury. Delayed management may give rise to a variety of complications in such a peculiar case. Fortunately, this child is healthy, leading a normal life with no complications.